On the Basic Concepts of Hydrobiology - Alexander А. Protasov (Журнал Сибирского федерального университета: Серия Биология, 2010)
The basic concepts of hydrobiology are considered. Interrelations of hydrobiology with ecology are discussed, questions of the terminology concerning designations of some sections of hydrobiology are considered. Interrelations of hydrobiology and the doctrine about biosphere are considered.